방파제용 대형 케이슨 제작/진수에 따른 부양식 독의 안정성 해석 - 석준(Jun Seok); 박종천(Jong-Chun Park); 정세민(Se-Min Jeong); 김성용(Sung-Yong Kim); 강헌용(Heon-Yong Kang); Moo-Hyun Kim; 강윤구(Yoon-Koo Kang) (Han-guk haeyang gonghak hoeji (Online), 2013)
In general, huge caissons for breakwaters have been constructed on land or a floating dock. In the case of the construction on a floating dock, a 4 step installation procedure is involved: i) construction on a floating dock, ii) transportation by the floating dock to an area near the target sea, iii) launching from the floating dock, and iv) transference by tug-boats to the installation site. It is especially important to pay attention to the dynamic stability of the floating dock against the conditions in the sea during steps i) and iii). In this paper, the static and dynamic stabilities of a caisson on a floating dock are evaluated based on IMO rules during the construction and launching of the caisson on a floating dock by using independent commercial S/Ws such as NAPA, WAMIT, and CHARM3D.